COMBINATION OF CRYPTOGRAPHIC ALGORITHM AND STEGANOGRAPHY TO HIDDEN MESSAGE IN IMAGE - Yuliana Yuliana; I Wayan Pandu Swardiana; Dony Ariyus (Institut Teknologi Dirgantara Adisutjipto, 2019)
Along with the increasing use of the internet in Indonesia, the threat to messages in image media has increased. The confidential data that will be sent requires security so that it can be read by the recipient of the message. For this reason, it is necessary to design a security system for this picture's media message by encrypting and decrypting it then then hiding the message. The algorithm used by combining various cryptographic algorithms and steganography techniques using the LSB method. The test results show the security of the message on the image media, especially in protecting the copyright rights of the image. The original original image measuring 242 kb in the .jpg format will increase in value after adding secret data with a size of 536 kb using the .png format. This system successfully displays secret messages in the image and does not change the cover of the image.